2021
DOI: 10.1016/j.amsu.2021.102474
|View full text |Cite
|
Sign up to set email alerts
|

Bone choristoma of the gingiva: A case report

Abstract: Introduction Bone choristoma is a benign tumor with normal histology and ectopic location. This paper aims to report a rare case of bone choristoma in the maxillary gingival location. Observation The authors report a case of a 39-year-old woman, with a history of maxillary full edentulousness, who consulted for a slight pain evolved for about six months, triggered by movements on the lesion. Clinical examination found growth at the level of the right maxillary gingival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Osseous choristoma of the palate was mentioned previously in three separate reports, which makes our report the fourth one in the list. Other studies reported this lesion in less common sites, including gingiva, 11–15 alveolar mucosa, 16 submental region, 17,18 submandibular region, 19 masseter, 20 medial aspect of the lateral pterygoid, 21 lips, 22,23 and tonsils 24 …”
Section: Discussionmentioning
confidence: 97%
“…Osseous choristoma of the palate was mentioned previously in three separate reports, which makes our report the fourth one in the list. Other studies reported this lesion in less common sites, including gingiva, 11–15 alveolar mucosa, 16 submental region, 17,18 submandibular region, 19 masseter, 20 medial aspect of the lateral pterygoid, 21 lips, 22,23 and tonsils 24 …”
Section: Discussionmentioning
confidence: 97%
“…Excisional biopsy is routinely performed in humans with oral and maxillofacial lesions and has also been performed in dogs and cats. [20][21][22][23][24][25][26][27][28][29][30][31][32][33] The principal differential diagnoses for the dogs of this study with CAA included squamous cell carcinoma (SCC) and peripheral odontogenic fibroma (POF). For patients without a preoperative histopathology report and without exact knowledge of the tumor type, clients were counseled on excisional and incisional biopsy procedures.…”
Section: Discussionmentioning
confidence: 99%